Optical color image encryption based on Hadamard single-pixel imaging and Arnold transformation. (February 2021) - Qu, Gang; Meng, Xiangfeng; Yin, Yongkai; Wu, Huazheng; Yang, Xiulun; Peng, Xiang; He, Wenqi
Highlights: An optical color image encryption based on Hadamard single-pixel imaging and Arnold transformation is proposed. Due to the orthogonality of Hadamard matrix, Hadamard single-pixel imaging can achieve high quality imaging even undersampling. A coefficient matrix key is used to control both the quantity information of the color components and the parameters of the Arnold transformation, which increases the security of the optical cryptosystem. Abstract: An optical color image encryption method based on Hadamard single-pixel imaging (SPI) and Arnold transformation is proposed, in which, optical full-color image encryption with good imaging quality and high security performance can be accomplished by only one bucket detector (BD). In the encryption process, after controlling and modulating the Hadamard matrix by the coefficient matrix key, three different sets of colored Hadamard patterns are generated to be projected onto the target colored object; Subsequently, the collected experimental data: R, G, and B components are detected by a BD, which are then scrambled by Arnold transformation to further increase the security; Finally the colored ciphertext image can be recombined and obtained to transferring to the receivers. During the decryption, with the colored ciphertext and all the corrected keys, the original secret color image can be successfully decrypted by the extraction of R, G, B components, inverse Arnold transformation, the correlated computation in SPI, and inverse Hadamard transformation. The feasibility of this method and its robustness against some types of attacks are verified by both computer simulations and optical experiments.